2021
DOI: 10.1053/j.gastro.2021.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific Trends in Colorectal Cancer Incidence for Women and Men, 1935–2017

Abstract: A lthough colorectal cancer (CRC) incidence has decreased over time in adults aged 50 years, largely due to advancements and uptake in screening, incidence has dramatically increased over the past 4 decades in adults aged < 50 years in the United States. 1 Previous studies have only evaluated age-specific trends in CRC incidence from the mid-1970s or later, providing only a few years of data before the documented increase in early-onset CRC. This makes it difficult to establish the temporal relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Notwithstanding cases in all countries are on the rise, most CRC cases occur in Western countries, where there is an increase in incidence[ 28 ]. CRC rates in older adults in the United States have declined in recent years probably due to increased screening, but rates in younger adults have been rising, which may be correlated with higher incidence of obesity and other diet and lifestyle trends in the western hemisphere[ 29 ].…”
Section: Crc and Gut Microbiotamentioning
confidence: 99%
“…Notwithstanding cases in all countries are on the rise, most CRC cases occur in Western countries, where there is an increase in incidence[ 28 ]. CRC rates in older adults in the United States have declined in recent years probably due to increased screening, but rates in younger adults have been rising, which may be correlated with higher incidence of obesity and other diet and lifestyle trends in the western hemisphere[ 29 ].…”
Section: Crc and Gut Microbiotamentioning
confidence: 99%
“…Incidence of early‐onset colorectal cancer (EOCRC)—typically defined as colorectal cancer (CRC) diagnosed before age 50—has increased alarmingly in many countries including the United States (US) in recent decades 1–5 . A few recent studies, including our own, 6 have identified several risk factors of EOCRC, including alcohol drinking, 6,7 smoking, 8 red and processed meat intake, 8,9 low calcium intake, 10 and obesity 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Statistics regarding gastrointestinal cancer, and particularly colorectal cancer, indicate an increase in cancer incidence among people aged below 50 over the past four decades. 1 In the United States, the number of early-onset cancer cases is approximately 10.5% of the total new cases. 2 Many factors could contribute to this unprecedented rise, such as dietary habits, molecular and genetic profiles, and sedentary lifestyle.…”
Section: Introductionmentioning
confidence: 99%